Sharing economy: A potential new pathway to sustainability. - Heinrichs, Harald (Oekom, 2013)
Despite the success of some environmental and sustainability initiatives and measures in policy-making, business and society, overall trends follow an unsustainable path. Especially in the field of production a rid consumption of goods and services, environmental sustainability and social equality remain critical challenges. Therefore new approaches are needed alongside existing strategies and policy instruments. The sharing economy has the potential to provide a new pathway to sustainability and transdisciplinary sustainability science has the opportunity to co-shape and accompany this pathway.
Keywords: Wirtschaftsentwicklung; Wirtschaftswachstum; Umweltbewusstsein; Ressourcen; Recycling; Gemeinschaftsnutzung; Ökologie; Verbraucherverhalten; Partizipation; Nachhaltigkeit